Clinical Features and Risk Factors of Fungal Peritonitis in Children on Peritoneal Dialysis - Fang, Xiaoyan; Cui, Jingyi; Zhai, Yihui; Liu, Jiaojiao; Rao, Jia; Zhang, Zhiqing; Chen, Jing; Liu, Jialu; Miao, Qianfan; Shen, Qian; Xu, Hong (Frontiers in Pediatrics, 2021)
Objective: To analyse the clinical manifestations, aetiology, prognosis, and risk factors of fungal peritonitis (FP) in children on peritoneal dialysis (PD). Methods: Among 322 children undergoing PD at Children's Hospital of Fudan University, between January 2001 and December 2019, FP cases were retrospectively analysed and compared with those of bacterial peritonitis (BP) to analyse the risk factors of FP. Results: A total of 124 cases of peritonitis were treated, including 11 FP cases in 11 children (0.0019 episodes/patient*month) and 113 BP cases in 64 children (0.02 episodes/patient*month). Among the 11 FP cases, 7 (63.64%) were caused by Candida and Candida parapsilosis (5/11) was the most common pathogen. All FP patients were converted to haemodialysis (HD) and did not resume PD during follow-up. Two patients (18.2%) died after 6 months of HD due to heart failure, 2 patients underwent kidney transplant after 2 years of infection, and the other 7 patients were still on HD. The univariate analysis showed the usage rate of antibiotics in the month before the onset of peritonitis was higher (45.45% vs 15.93%) and the mean serum albumin was lower (31.4 g/L vs 34.4 g/L) in the FP group when compared with BP group (P < 0.05), while multivariate analysis showed that serum albumin ≤ 30g/L was an independent risk factor for FP (odds ratio 4.896, 95% confidence interval 1.335 - 17.961). Conclusion: FP is a rare complication of PD in children, but is associated with high technique failure. Attention should be paid to hypoproteinaemia and antibiotic use in children on PD.